Pengaruh Ukuran Perusahaan, Leverage dan Profitabilitas terhadap Manajemen Laba dengan Kompensasi Bonus sebagai Variabel Moderating - Nurul Azizah Adyastuti; Muhammad Khafid (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to find empirical evidence regarding the effect of firm size, leverage and profitability on earnings management with bonus compensation as a moderating variable. A total of 194 manufacturing companies listed on the Indonesia Stock Exchange during the period 2018 to 2019 were used as the study population. Purposive sampling was used as a sampling method which obtained 87 companies with 126 units of analysis. Data collection in the study was carried out using the documentation method. This study uses the method of moderated regression analysis (MRA) which is processed through IBM SPSS Statistics 21 software. This study proves empirically that there is a negative effect between firm size on earnings management, and there is a positive effect between profitability on earnings management and there is no influence between leverage to earnings management. Furthermore, bonus compensation can be used to moderate the effect of profitability on earnings management, but cannot moderate the effect of firm size and leverage on earnings management. The conclusion of this study is earnings management practices will increase when the company has a high level of profitability. High profitability from management tends to maximize profits by maximizing bonuses received by managers, increasing company performance so that it looks good and gains the trust of investors.